2015
DOI: 10.4269/ajtmh.13-0677
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Risk Factors of Soil-Transmitted Helminthiasis Among Orang Asli Subgroups in Peninsular Malaysia

Abstract: Abstract. A cross-sectional study was conducted to provide comprehensive data on the patterns and associated risk factors of soil-transmitted helminth (STH) infections among five Orang Asli subgroups in Peninsular Malaysia. The overall prevalence of STH infections was 59.9% (95% confidence interval [CI] = 56.1-63.7%). Trichuris trichiura (54.3%; 95% CI = 50.4-58.2%) was the predominant species followed by Ascaris lumbricoides (26.7%; 95% CI = 23.3-30.1%) and hookworm (9.1%; 95% CI = 6.9-11.3%). This study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 35 publications
8
35
3
1
Order By: Relevance
“…The findings of the present study showed a high prevalence of IPIs with 57.5% of participants was infected with at least one species. These findings in a state in Borneo Malaysia were relatively consistent to the report from previous study among indigenous groups in Peninsular Malaysia with prevalence rates of 50% and above [2,4,7,1921]. Similarly, the results were also consistent with previous local study conducted among other indigenous community in Saratok Division which reported high prevalence of IPIs (67.6%) [28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the present study showed a high prevalence of IPIs with 57.5% of participants was infected with at least one species. These findings in a state in Borneo Malaysia were relatively consistent to the report from previous study among indigenous groups in Peninsular Malaysia with prevalence rates of 50% and above [2,4,7,1921]. Similarly, the results were also consistent with previous local study conducted among other indigenous community in Saratok Division which reported high prevalence of IPIs (67.6%) [28].…”
Section: Discussionsupporting
confidence: 91%
“…Although Malaysia has undergone rapid growth in socioeconomic and development infrastructure, IPIs and malnutrition are still endemic particularly among the underprivileged indigenous communities which are closely associated with their poor socioeconomic status (SES), personal and environmental hygiene [2,4,7,1721]. Malaysia consists of Peninsular Malaysia and Borneo Malaysia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the span of previous study and the current study is over 20 years, and both studies have the limitation of small sample size, we are unable to conclude whether there is a true reduction in seroprevalence among the aborigines and whether modernization of lifestyles contributes to the reduction. Eating with hands without proper hand washing, walking barefoot and poor surrounding sanitation evident among the aborigines reported by other researchers study (Ngui et al, ) was also observed in this study. Future larger scale studies are needed to confirm this and to also investigate the possible reasons.…”
Section: Discussionsupporting
confidence: 87%
“…In this study different factors had association with the increase prevalence of hookworm after multivariate analysis. This study revealed that absence of shoe wearing habit was significantly associated with hookworm infection (AOR = 3.9; 95% CI = ( 1.11-14.24) This study finding was supported by a study conducted in Wolaita Zone Southern Ethiopia [10], and Orang Asli in Peninsular Malaysia [22]. This factor is an important evidence for the high prevalence of hookworm because the transmission of the parasite is through penetration of skin by the infective filariform larvae and prevented by reduction of skin contact with potentially infected soil by wearing shoes [1].…”
Section: Discussionsupporting
confidence: 64%